SYMBOLIC LANDSCAPE OF CONSCIOUSNESS: MAN BETWEEN REPRESENTATIONALISM, FUNCTIONALISM AND RELATIVISM - P. V. Kretov; O. I. Kretova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The aim of the study is to clarify the changed interpretation of symbol in the context of the ontological turn in cultural anthropology and philosophical anthropology and their correlation with the functioning of the semantic field of culture, and in particular with religious symbols. The paper also considers an epistemological-ideological positions of representationalism, functionalism and relativism with respect to philosopheme of symbol. Methodology. The authors implemented theoretical and conceptual analysis in synchronic and diachronic aspects, the methodology of comparative consideration of the character within the analytical and existential paradigms in the 20th century philosophy. Originality. The work presents the study of correlation between aspect consideration of the nature and specific character in representationalism, functionalism and relativism within the philosophical projects of the cognitive position. The authors substantiated the position of symbol ontologization in the contemporary cultural and philosophical anthropology and the importance of convergence of the symbol concept and philosopheme with the concepts of an object and a thing. They fixed the value of the ontological turn in cultural anthropology for philosophical anthropology. The authors specifically examined the correlation between the declared symbol interpretation, project of object-oriented ontology and the modern philosophy of science. They substantiated ontological concept of symbolic landscape of modern philosophical anthropology, social philosophy and philosophy of mind. The symbol and religious symbolism have the significant importance for human identity, the symbol is considered to be the tool of human’s self-knowledge. Conclusions. The paper outlines the specific character of existence of symbol philosopheme in communicative field of modern man, the social media space, in particular the role of religious symbols for the construction of identity and self-positioning of modern man.